Determination Factors of Elderly Decision to Keep Continuing Work Activities in Palembang City - Hendry Wijaya; Nurlina T. Muhyiddin; Bambang Bemby Soebyakto; Saadah Yuliana (International Review of Management and Marketing, 2019)
This research study focuses on the determination of the factors of the elderly decision to keep continuing work activities in Palembang city. The research unit is the elderly who still work in the city of Palembang with a total sample of 395 respondents. The method of data analysis is using binary logistic regression method. The results of the data estimation, it is known that all of independent variables have a significant influence on the dependent variable. Odds Ratio of 7.672 means that the elderly population has a probability men choose to remain employed by 7.672 times. Odds ratio of 4.511 means that senior citizens get social support has a probability of choosing to keep working at 4.511 times. Odds ratio of 3.202 means that elderly people who have the burden of family responsibility has a probability to choose to keep working at 3.202 times. Nagelkerke's R-square value is 0.281.